2021
DOI: 10.1021/acs.inorgchem.1c00236
|View full text |Cite
|
Sign up to set email alerts
|

All Four Atropisomers of Iron Tetra(o-N,N,N-trimethylanilinium)porphyrin in Both the Ferric and Ferrous States

Abstract: Electrostatic effects are key to many biological and (electro)­chemical transformations, especially those that involve charged species. The position and orientation of the electric field with respect to the molecules undergoing charge rearrangement are often crucial to the progress of the reaction. Recently, several molecular (electro)­catalysts have been designed to contain spatially positioned charged groups that can engage in specific intramolecular electrostatic interactions. For instance, iron complexes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 52 publications
(117 reference statements)
1
17
0
Order By: Relevance
“…11). [69][70][71][72] The authors found no catalytic improvement over other iron porphyrin electrocatalysts, corroborating the study discussed above in which O 2 binding was (nearly) unaffected by the presence of cationic groups in the secondary coordination sphere. 68 Previous studies with iron porphyrin ORR electrocatalysts established scaling relationships between log(TOF max ) and effective overpotential under various reaction conditions, wherein changes in acid concentration, acid pK a , O 2 concentration, or catalyst E 1/2 values led to increases in log(TOF max ) at the expense of effective overpotential, or vice versa.…”
Section: Molecular Electrostatic Effects In Small Molecule Activation...supporting
confidence: 76%
“…11). [69][70][71][72] The authors found no catalytic improvement over other iron porphyrin electrocatalysts, corroborating the study discussed above in which O 2 binding was (nearly) unaffected by the presence of cationic groups in the secondary coordination sphere. 68 Previous studies with iron porphyrin ORR electrocatalysts established scaling relationships between log(TOF max ) and effective overpotential under various reaction conditions, wherein changes in acid concentration, acid pK a , O 2 concentration, or catalyst E 1/2 values led to increases in log(TOF max ) at the expense of effective overpotential, or vice versa.…”
Section: Molecular Electrostatic Effects In Small Molecule Activation...supporting
confidence: 76%
“…Reported homogeneous transition metal complexes with charged functionalities that contribute to changes in electronic structure or reactivity. Left, top-to-bottom: Agapie (refs and ), Gilbertson (ref ), Mayer (ref and ), Groves (refs and ), Shaik (ref ), McCrory (ref ); Right, top-to-bottom: Tomson (ref ), Savéant (ref ), Warren (ref ), Tolman (ref ), Wiedner (ref ).…”
Section: Synthetic Systemsmentioning
confidence: 99%
“…For the former, computational studies indicate the cationic functionalities stabilize anionic intermediates . In the latter example, the proximal cations play a complex role in pre-equilibria substrate binding due to through-space electrostatic and inductive contributions. , Additionally, Groves and co-workers reported Fe porphyrin complexes with cationic porphyrins that were exceptionally active for C–H activation. , A subsequent computational study by Shaik and co-workers indicated that the electric field generated by the cationic functionalities selectively destabilized the reactants more than the transition states, leading to the accelerated rate …”
Section: Synthetic Systemsmentioning
confidence: 99%
“…Similar issues have been described for 4-fold symmetric iron complexes used for CO 2 and O 2 reduction. 122,123 One approach to avoiding the problem of conformational complexity is to carry out calculations using small, inflexible ligands, e.g., formate groups, acetate groups, or truncated chiral ligands. While this approach is often reasonable, one must be exceedingly cautious when employing it to assure that important substrate-ligand interactions are not missed and that the shape of the catalyst cavity is not compromised.…”
Section: Conformations and Ligand-binding Modesmentioning
confidence: 99%